2022
DOI: 10.1177/00472875211073976
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Gender Gap in the Propensity to Travel of People With Disabilities?

Abstract: People with disabilities (PwDs) face various constraints connected to their participation in tourism activities. This topic has become of greater academic interest in recent years, however, the study of gender issues in this context is still marginal. The present paper seeks to analyze gender differences in PwDs’ propensity to travel, explicitly examining constraints that may limit social inclusion in tourism activities. The empirical analysis is focused on sample data of the Italian population of PwDs gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…The literature shows that women with disabilities are doubly disadvantaged because of gender and disability-related exclusion (De Pascale et al. , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The literature shows that women with disabilities are doubly disadvantaged because of gender and disability-related exclusion (De Pascale et al. , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Gender goes beyond the limits of biology, and it is also constructed by prevailing social and cultural norms ( De Pascale et al, 2022 ). It is clear from the extant literature that gender has been used for tourism market segmentation, but the relationship between gender and travel behaviors is largely neglected ( Huang and van der Veen, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Yamashita and Hallmann (2021) revealed that there are obvious gender differences concerning the relationship between travel constraints and behavioral intentions. Specifically, De Pascale et al (2022) found that the propensity to travel for females with disabilities is more affected by some travel constraints than it is for males with disabilities. It is thought that analyzing gender is crucial to understand and interpret leisure constraints in a selected context ( Jackson and Henderson, 1995 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Department of Statistics Malaysia (2021), the COVID-19 epidemic reduced Malaysia's tourist earnings in 2020 to RM52.4 billion, a 71.2% decline from 2019. During the pandemic crisis, those with disabilities suffer greatly (De Pascale et al, 2022). Furthermore, Hashim et al (2018) contend that prejudice and hurdles prevent Malaysians with disabilities from fully participating in society.…”
Section: Introductionmentioning
confidence: 99%